Cohort profile: the China Ageing REespiratory infections Study (CARES), a prospective cohort study in older adults in Eastern China. Issue 10 (1st November 2017) - Cowling, Benjamin J; Xu, Cuiling; Tang, Fenyang; Zhang, Jun; Shen, Jinjin; Havers, Fiona; Wendladt, Rachael; Leung, Nancy HL; Greene, Carolyn; Iuliano, A Danielle; Shifflett, Pat; Song, Ying; et al.
Abstract : Purpose: This study was established to provide direct evidence on the incidence of laboratory-confirmed influenza virus and respiratory syncytial virus (RSV) infections in older adults in two cities in Jiangsu Province, China, and the potential impact of acute respiratory infections on frailty. Participants: The cohort was enrolled in Suzhou and Yancheng, two cities in Jiangsu Province in Eastern China. Between November 2015 and March 2016, we enrolled 1532 adults who were 60–89 years of age, and collected blood samples along with baseline data on demographics, general health, chronic diseases, functional status and cognitive function through face-to-face interviews using a standardised questionnaire. Participants are being followed weekly throughout the year to identify acute respiratory illnesses. We schedule home visits to ill participants to collect mid-turbinate nasal and oropharyngeal swabs for laboratory testing and detailed symptom information for the acute illness. Regular follow-up including face-to-face interviews and further blood draws will take place every 6–12 months. Findings to date: As of 3 September 2016, we had identified 339 qualifying acute respiratory illness events and 1463 (95%) participants remained in the study. Laboratory testing is ongoing. Future plans: We plan to conduct laboratory testing to estimate the incidence of influenza virus and RSV infections in older adults. We plan to investigate the impact of these infections on frailty and functional status to determine the association of pre-existing immune status with protection against influenza and RSV infection in unvaccinated older adults, and to assess the exposure to avian influenza viruses in this population.